Factors Influencing Job Satisfaction: A Study on the Banking Sector Employees in the Sultanate of Oman - Shamsa Al Marhoobi; Muhamad Azrin Nazri; Subaashnii Suppramaniam (Asia Pacific University Sdn. Bhd., 2026)
Tier 4- Non-Indexed Publication